4CPS-139 Psychotropic drug usage in octogenarian and nonagenarian complex chronic patients. (24th March 2020) - Perez Contel, A; Ortonobes Roig, S; Soler Blanco, N; Diestre Ortin, G; Miralles-Albors, P; Fernández-Molina, S; Barragán Muñoz, A; Gómez-Valent, M
Abstract : Background and importance: Elderly patients often manifest behavioural disorders. They commonly involve the use of psychotropic drugs that are associated with drowsiness, confusion and risk of falls, especially in this vulnerable population. The significant increase in psychotropic drug consumption in recent years has promoted strategies to identify potentially inappropriate prescriptions and their optimisation or de-prescription. Aim and objectives: To estimate the prevalence of psychotropic drugs at discharge in geriatric patients and describe the most frequently prescribed. To evaluate differences between octogenarian and nonagenarian complex chronic patients (CCP). Material and methods: A retrospective observational study was conducted in geriatric patients discharged between May and June 2019 from an acute geriatric unit (41 beds) of a geriatric healthcare centre from a university hospital. Variables registered were age, sex, length of stay (LOS), and number and type of psychotropic drugs at discharge (hypnotics, antidepressants, neuroleptics, mood stabilisers). For octogenarian and nonagenarian CCP designated as primary care, we also collected data on polypharmacy and the Pfeiffer test before admission. Those who died were excluded. Quantitative data are presented as median (Q1–Q3) and we used the Mann–Whitney–Wilcoxon U test. Statistical analysis was performed with Stata13. Results: A total of 148 patients were included, 87 (58.8%) women, aged 86 (82.75–90.25) years. LOS was 9 (6–13.25) days. Prescription of psychotropic drugs was as follows: 68 (49.9%) patients received hypnotics (49/68 (72.0%) trazodone and 23/68 (33.8%) short/intermediate acting benzodiazepines); 46 (31.1%) received antidepressants (15/46 (32.6%) sertraline); 39 (26.3%) received neuroleptics (25/39 (64.1%) quetiapine and 13/39 (33.3%) risperidone); and 18 (12.2%) received mood stabilisers (8/18 (44.4%) gabapentin). The number of patients with at least one psychotropic prescription was 97 (65.5%) and 23 (15.5%) had ≥3 psychotropic prescriptions. Differences between octogenarian (n=29) and nonagenarian CCP (n=20) were: LOS 10 (7–13) versus 8 (5.5–16) days (p=0.554); number of psychotropic drugs 2 (1–3) versus 1.5 (0–2) (p=0.378); polypharmacy 12 (10–14) versus 11 (8.5–12) drugs (p=0.135); and Pfeiffer test 2 (0–4) versus 3 (1–7) points (p=0.08). Conclusion and relevance: Two–thirds of patients were receiving treatment with at least one psychotropic drug, with hypnotics and antidepressants the most prescribed. The small sample size made it difficult to demonstrate statistically significant differences, but this study suggests that nonagenarian CCP present less polypharmacy and a lower number of psychotropic drugs compared with octogenarian CCP, despite having higher cognitive impairment. References and/or acknowledgements: No conflict of interest.